Association of Maternal Body Mass Index With Risk of Infant Mortality: A Dose-Response Meta-Analysis - Nana Huo; Kun Zhang; Li Wang; Lina Wang; Wenhui Lv; Wenke Cheng; GuangZhu Jia (Frontiers Media S.A., 2021)
Objective: This study presumed that a high or low body mass index (BMI) might increase the risk of infant mortality. Therefore, a meta-analysis was performed to systematically assess the association between maternal BMI and the risk of infant mortality.Methods: The electronic databases, including Pubmed, Embase database, and Cochrane Library, were systemically searched by two investigators from inception to November 26th, 2020, with no language restriction. In parallel, a dose-response was assessed.Results: Finally, 22 cohort studies involving 13,532,293 participants were included into this paper, which showed that compared with normal BMI, maternal overweight significantly increased the risks of infant mortality [risk ratio (RR), 1.16; 95% confidence interval (CI), 1.13-1.19], neonatal mortality (RR, 1.23; 95% CI, 1.08-1.39), early neonatal mortality (RR, 1.55; 95% CI, 1.26-1.92) and post-neonatal mortality (RR, 1.18; 95% CI, 1.07-1.29). Similarly, maternal obesity significantly increased the risk of infant mortality (RR, 1.55; 95% CI, 1.41-1.70), neonatal mortality (RR, 1.55; 95% CI, 1.28-1.67), early neonatal mortality (RR, 1.37; 95% CI, 1.13-1.67), and post-neonatal mortality (RR, 1.30; 95% CI, 1.03-1.65), whereas maternal underweight potentially decreased the risk of infant mortality (RR, 0.93; 95% CI, 0.88-0.98). In the dose-response analysis, the risk of infant mortality significantly increased when the maternal BMI was >25 kg/m2.Conclusions: Maternal overweight or obesity significantly increases the risks of infant mortality, neonatal mortality, early neonatal mortality, and post-neonatal mortality compared with normal BMI in a dose-dependent manner. Besides, maternal underweight will not increase the risk of infant mortality, neonatal mortality, early neonatal mortality, or postneonatal mortality; instead, it tends to decrease the risk of infant mortality. Early weight management may provide potential benefits to infants, and more large-scale prospective studies are needed to verify this finding in the future.